Anal and Cervical High-Risk Human Papillomavirus Genotyping in Women With and Without Genital Neoplasia. Issue 2 (April 2018) - Bregar, Amy J.; Cronin, Beth; Luis, Christine; DiSilvestro, Paul; Schechter, Steven; Pisharodi, Latha; Raker, Christina; Clark, Melissa; Robison, Katina
Abstract : Objective: The aim of the study was to compare the prevalence, genotypes, and rates of concomitant anal and cervical high-risk human papillomavirus (HR-HPV) in women with and without a history of HPV-related genital neoplasia. Materials and Methods: This was a prospective cohort study conducted from December 2012 to February 2014. Women with a history of neoplasia were considered the high-risk group. Women without a history of neoplasia were considered the low-risk group. Cervical and anal cytology and HPV genotyping were performed. All women with abnormal anal cytology were referred for anoscopy. Results: One hundred eighty-four women met inclusion criteria. High-risk HPV was detected in the anal canal of 17.4% of the high-risk group and 1.5% of the low-risk group ( p = .003). High-risk HPV was detected in the cervix of 30.5% of the high-risk group and 7.6% of the low-risk group ( p < .001). Concomitant anal and cervical high-risk HPV was detected in 4.4% of the high-risk group and was not detected in the low-risk group ( p = .2). Among women with anal intraepithelial neoplasia 2 or greater (n = 5), 60% had HR-HPV detected in the anal canal while none had HR-HPV detected in the cervix. Conclusions: Women with a history of genital neoplasia are more likely to be positive for anal and cervical HR-HPV compared with women without a history of genital neoplasia. Although there was no significant difference in rates of concomitant HR-HPV between low- and high-risk groups, HR-HPV can be found concomitantly in the anus and the cervix and may be associated with anal intraepithelial neoplasia or carcinoma.